DAMPAK SELF CONTROL DAN SELF ESTEEM TERHADAP FEAR OF MISSING OUT (FoMO) PADA MAHASISWA PENGGUNA MEDIA SOSIAL INSTAGRAM DI UNIVERSITAS JENDERAL SOEDIRMAN - Sheila Pradani Agustine Priyono; Dyah Astorini Wulandari; Rr. Setyawati; Fatin Rohmah Nur Wahidah (CV. Denasya Smart Publisher, 2025)
College students are at a developmental stage that is vulnerable to social pressure, including the demand to follow trends and activities displayed on social media such as Instagram. In this situation, self control and self esteem skills are needed so that students do not easily experience Fear of Missing Out (FoMO), which is a feeling of anxiety when feeling left behind from the experiences of others. This study aims to determine the effect of self control and self esteem on Fear of Missing Out (FoMO) in student Instagram users at Jenderal Soedirman University. The method used is a quantitative approach involving 377 respondents selected through accidental sampling technique. Data were collected using a self control scale, a self-esteem scale, and a Fear of Missing Out (FoMO) scale. The results of the analysis showed a t value = -2.011 for the effect of self control on Fear of Missing Out (FoMO) and t = -2.720 for the effect of self esteem on Fear of Missing Out (FoMO). The F value = 3.760 indicates a significant influence between self-control and self esteem on Fear of Missing Out (FoMO). With an R Square of 0.020, this study shows that self control and self esteem contribute 2% to Fear of Missing Out (FoMO), while 98% is influenced by other factors not examined. These findings emphasize the importance of strengthening self control and self esteem to reduce anxiety caused by social media.